PENGARUH TERAPI BERMAIN PUZZLE TERHADAP PERKEMBANGAN MOTORIK HALUS PADA ANAK PRASEKOLAH USIA 3-5 TAHUN - Tantri Wenny Sitanggang; Dewi Anggraini; Intan Puspitasari (Jurnal Medikes (Media Informasi Kesehatan), 2022)
In Indonesia, the proportion of children who have impaired fine motor development is 9.8%. Fine motor skills can be developed through play activities that involve small muscles, and eye and hand coordination (such as puzzles). This study aims to determine the effect of playing puzzle therapy on fine motoric development in preschool children aged 3-5 years at the Posyandu, Pondok Ranji Village. Research methods using the One Group Pretest-Posttest approach. The sample in this study was 23 children. The sampling technique used cluster sampling. Methods of data analysis using the Wilcoxon Signed-Rank test. There were 8 children (34.8%) with a mean value of 1.35 who had normal fine motor development before doing puzzle playing therapy. There were 19 children (82.6%) with a mean value of 1.70 who had normal fine motor development after playing puzzle therapy. The results of the study were that there was an effect of puzzle play therapy on fine motor development in preschool children aged 3-5 years at the Posyandu in Pondok Ranji Village with a p-Value of 0.001. It is hoped that puzzle playing therapy can be used as an alternative therapy for fine motor development in children that can be provided by family and health workers